Injuries of young elite female basketball players over a six-year period - Hickey, G. J.; Fricker, P. A.; McDonald, W. A. (Clinical Journal of Sport Medicine, 1997)
OBJECTIVE: To analyze injuries retrospectively among female basketball players at the Australian Institute of Sport (AIS) from 1990 to 1995 inclusive. DESIGN: The medical records of all the female basketball players on AIS (residential) scholarships were examined, and all injuries were recorded. SETTING: The Sports Medicine Department at the Australian Institute of Sport in Canberra, Australia. PARTICIPANTS: The participants were 49 elite female basketball players, holding full scholarships at the AIS, with an average age of 17.6 years at the time of injury presentation. MAIN OUTCOME MEASURES: Injury presentation according to region involved, nature of injury, and most common specific injuries (diagnoses). RESULTS: A total of 223 injuries were recorded: 139 were acute and 84 were chronic. The regions most frequently injured were the knee (18.8%), ankle (16.6%), lumbar spine (11.7%), and lower legs (10.8%). The most frequent diagnoses were ankle lateral ligament sprain (12.1%), patellar tendinitis (6.7%), lower limb stress fractures (5.4%), finger sprains (4.9%), and mechanical low back pain (4.5%). CONCLUSIONS: There was a high incidence of knee and ankle injury in this group of young elite female basketball players, and stress fractures were not uncommon. The incidence of injury in female basketball players may be increasing. Further research in this area may help reduce the risk of stress fractures and serious ankle and knee injuries.